Acute cholecystitis developed immediately after thoracic kyphoplasty -A case report - An, Sang-Bum; Yim, Jiyeon; Kim, Eunjung; Shin, Jae-Hyuck; Park, Soo Young; Lee, Sang Chul (Korean journal of anesthesiology, 2012)
Postoperative acute cholecystitis is a rare complication of orthopaedic surgery and is unrelated to the biliary tract. In particular, in the case of immediate postoperative state after surgery such as kyphoplasty at the thoracic vertebra, symptoms related to inflammation mimic those of abdominal origin, so the diagnosis and the treatment of acute cholecystitis can be delayed leading to a fatal outcome. It is important that physicians should be aware of the postoperative patient's condition in order to make an early diagnosis and determine treatment.